2012
DOI: 10.1007/bf03262871
|View full text |Cite
|
Sign up to set email alerts
|

Early prognostic indicators and outcome prediction model for replanted avulsed teeth

Abstract: These predictive models based on patient age, stage of root formation, storage medium, tooth mobility after dressing and tooth mobility after splinting were shown to have high predictive value and will enable a clinician to estimate the long term prognosis of avulsed and replanted teeth. It will enable planning for further treatment with a realistic view of outcome at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
2
2
1
Order By: Relevance
“…The pulp healing rate in this study is higher than those reported by Rhouma et al 20 and Wang et al 21 of 7.0% and 9.1%, respectively. However, this can be considered as a lower rate than that reported in previous studies, which reported pulp healing rates ranging from 18% to 34.8% 18,19,22–25 .…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…The pulp healing rate in this study is higher than those reported by Rhouma et al 20 and Wang et al 21 of 7.0% and 9.1%, respectively. However, this can be considered as a lower rate than that reported in previous studies, which reported pulp healing rates ranging from 18% to 34.8% 18,19,22–25 .…”
Section: Discussioncontrasting
confidence: 76%
“…While the first implies pulp survival with neural and vascular repair and the completion of root development, intracanal bone-like tissue is characterized by the presence of mineralized tissue inside the root canal space which is separated from the internal root surface together with the cessation of further root development. 26 The pulp healing rate in this study is higher than those reported by Rhouma et al 20 and Wang et al 21 of 7.0% and 9.1%, respectively.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The treatment was considered successful according to the following criteria: 1. patient without spontaneous pain; 2. color of the gingival was normal, no sinus tract; 3. no sensitive to percussion; 4. no loosening of the teeth or loosening at the Degree I; 4. radiological analysis demonstrated that radiolucent shadow around apex dispeared and there is no internal root resorption and external root resorption should be no more than 2 cm [17].…”
Section: Methodsmentioning
confidence: 95%
“…En las ultimas radiografías presentadas en caso abordado se logra apreciar mejor la leve reabsorción radicular externa (figuras 2c y 2d) la cual puede guardar una relación con el almacenamiento en medio seco según varias investigaciones 8,17,18 , en especial la de Rhouma, McMahon y Welbury 17 en Escocia donde de 16 dientes que se mantuvieron en un medio seco solo 6 de ellos pudieron continuar con su función en boca y no fracasaron después del reimplante, resultado que se soporta con un OR de 4,13 (IC 95% 1,33 -12,80). No obstante, en el presente reporte la reabsorción observada no comprometió la permanencia del diente en la arcada superior, desenlace que podría deberse a la inmersión del diente en fluoruro de sodio, tal y como lo reportan varias investigaciones en animales [19][20][21] .…”
Section: Discussionunclassified